Kebijakan Pertamina dalam Perdagangan Minyak Indonesia (1969–2015) - Sukusen Soemarinda; Yeremias T. Keban; Muhadjir Darwin; Tumiran Tumiran (Populasi, 2018)
Pertamina has a long history of oil trading and was influenced by the actors seizing for the power. The first oil shipments was held in 1958, while this research only discussesPertamina oil trading from 1969 to 2015 through a special subsidiary which was established to carry out the trading for almost fifty years since it was still named as Perta Group (1969) until Petral (2015). The purpose of this research is to know how Pertamina oil trading policy was specified and implemented over a period of time and parties affecting the process so rent- seeking and corruption happened throughout the history of Pertamina oil trading. The method of research a descriptive qualitative method of case study. The data was collected from various documents and interview of perpetrators related. Based on the research carried out, Pertamina oil trading from Perta Group (1969) until Petral (2015) could be classified into three periods, i.e. Perta Group period (1969-1978), POML period (1978-1998), and Petral (1998-2015). The first and second period occurred under the authority of the New Order government, while the third period under the reformation periodThe first period was characterized by the domination of military interests and the second period influenced by the interests of inner circle and family business related to the ruler of the New Order and the third period was dominated by the influence of powerfull person/company.